School Principal’s Strategy in Developing Teacher’s Professional Competencies to Improve Educational Quality - Riyany, Evy; Harapan, Edi; Tahrun, Tahrun (Journal of Social Work and Science Education, 2020)
This study identified the principal's strategy in developing teacher’s professional competence. This research used a qualitative approach with descriptive methods. Data collection techniques are carried out through interviews, observation and documentation. The research subjects were the principal and teachers of SD Negeri 1 Kota Prabumulih. The results showed that: (1) in order to improve and develop the professional competence of teachers in SD Negeri 1 Kota Prabumulih, the head seems to implement and implement a strategy in the form of "Supervision"; (2) teacher competence at SD Negeri 1 Kota Prabumulih is quite good. because teachers have been trained to educate, teach, guide, direct, train, assess, and evaluate students, and (3) obstacles faced by school principals in improving the professional competence of SD Negeri 1 Prabumulih City teachers, namely: teachers have a solid job in teaching in the classroom so that the teacher does not pay attention to the supervision carried out by the principal, sometimes less and unscheduled implementation time is caused by the principal's busyness in attending official events and meetings outside of school, and some teachers are still there who are late or do not comply with the stipulations on the right time in making the Lesson Plan.